ART DÉCO IN CAMPINA GRANDE: APPRECIATION, RECOGNITION AS HERITAGE AND OBLIVION - Dantas de Queiroz, Marcus Vinicius (Revista UFG, 2017)
Jackson do Pandeiro’s memories of childhood and youth, a recurring theme in his musical world, evoke sounds of the coconut instrumentalists at the Campina Grande Market, the smells of the wares on display, the songs of the casinos, the accents of a city with cosmopolitan airs, the swims in the Bodocongó dam, the gulps of white rum taken in the pubs among the brothels, the disturbances, the racket and stabbings in forrós and cabarets, sleepless nights in prostitutes’ beds. The frenetic pace of the then beginner tambourine player would seem to harmonize with a rapidly expanding and changing landscape throughout the 1930s and 1940s. (...)